Pengembangan Critical Thinking Dalam Peningkatan Mutu Pendidikan di Indonesia - Atris Yuliarti Mulyani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Critical thinking is the ability to think that exists in students. This ability helps students face every problem using scientific thinking. Critical thinking consists of the words